Microbial Diversity in Moonmilk of Baeg-nyong Cave, Korean CZO - Park, Shinae; Cho, Yong-Joon; Jung, Da-yea; Jo, Kyung-nam; Lee, Eun-Jin; Lee, Jung-Shin (Frontiers in Microbiology, 2020)
The Baeg-nyong cave is a limestone cave which has been nominated as the first critical zone observatory (CZO) in South Korea. Moonmilk is a well-known speleothem composed of various carbonate minerals. To characterize moonmilk from the Baeg-nyong cave, we performed mineralogical analyses and applied high-throughput 16S rRNA gene sequencing to analyze the microbial communities, including bacteria and fungi, of dry and wet moonmilk samples. The results showed that the dry and wet moonmilk samples had different and atypical crystal structures, although they were predominantly composed of CaCO3. Furthermore, metagenomic data revealed that the dry and wet moonmilk samples collected from an oligotrophic environment had completely different bacterial communities when compared to the outside soil, and there was a difference in bacterial communities even between dry and wet moonmilk specimens. Fungal communities, however, did not differ significantly between dry and wet moonmilk samples. This study is the first metagenomic analysis of two different types of moonmilk with different physical properties and the first report on the microbial diversity of moonmilk from a cave in the first CZO in South Korea.